(untitled) (Canadian Medical Education Journal, 2017)
Introduction: Global health addresses health inequities in the care of underserved populations, both domestic and international. Given that health systems with a strong primary care foundation are the most equitable, effective and efficient, family medicine is uniquely positioned to engage in global health. However, there are no nationally recognized standards in Canada for postgraduate family medicine training in global health. Objective: To generate consensus on the essential components of a Global Health/Health Equity Enhanced Skills Program in family medicine. Methods: A panel comprised of 34 experts in global health education and practice completed three rounds of a Delphi small group process. Results: Consensus (defined as ≥ 75% agreement) was achieved on program length (12 months), inclusion of both domestic and international components, importance of mentorship, methods of learner assessment (in-training evaluation report, portfolio), four program objectives (advocacy, sustainability, social justice, and an inclusive view of global health), importance of core content, and six specific core topics (social determinants of health, principles and ethics of health equity/global health, cultural humility and competency, pre and post-departure training, health systems, policy, and advocacy for change, and community engagement). Conclusion: Panellists agreed on a number of program components forming the initial foundation for an evidence-informed, competency-based Global Health/Health Equity Enhanced Skills Program in family medicine.